Przestępstwa przeciwko zdrowiu i życiu – noworodki, niemowlęta i dzieci jako ofiary zabójstw - Przybylska, Katarzyna (Kortowski Przegląd Prawniczy, 2022)
The history of the murder of children, infants and newborns is as long as the history of world. From the moment when people began to create communities, there were various types of crimes against members of the community. Infanticide in the primitive period was a kind of act of necessity from the point of view of a social group. In this way, the number of individuals burdensome for this group was reduced by eliminating weak or defective individuals, whose upbringing was an unacceptable burden for the group. Currently, crimes committed against children arouse the most negative feelings in us and the perpetrators of such crimes can count on severe punishments and long sentences. The presented statistics from the Polish and from the USA show that children are very often victims of crimes. Depending on their age use to different methods of punishment and the murders. The same situation is about the person, who commit the crime. On the first hours of life the newborn child the most often the abuser is the mother. When the child is growing the abuser can be father, babysitter or his siblings. It is worth to notice that in Poland we have a lot of crimes detect, but not confirmed and brought to specific charges. The history of the murder of children, infants and newborns is as long as the history of mankind, but the most disturbing is the fact that despite the advanced civilizational activity, the number of convicted people who commit such an act is growing.